2009
DOI: 10.1111/j.1444-0938.2008.00343.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional deficits in early stage age‐related maculopathy

Abstract: Background: It is of interest to examine paracentral functional deficits in early agerelated maculopathy (ARM), as histopathological studies indicate that this is where the earliest changes occur. The purpose of this study is to detect the sensory functional deficits at chosen retinal areas around the fovea and at the fovea itself in patients with early age-related maculopathy and to determine the type of functional losses that are more pronounced in early ARM. Methods: Ten participants with early ARM and 10 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…For the purposes of detecting refractive error, they have been shown to be sensitive to optical defocus as a result of spatial frequency phase reversals 14. However, these conventional letters appear to be relatively poor indicators of visual loss in early and intermediate age-related macular disease 4 15. Klein et al 16 reported a decrease in VA of only two or fewer letters for patients displaying early age-related maculopathy lesions compared with eyes without such early lesions.…”
Section: Introductionmentioning
confidence: 99%
“…For the purposes of detecting refractive error, they have been shown to be sensitive to optical defocus as a result of spatial frequency phase reversals 14. However, these conventional letters appear to be relatively poor indicators of visual loss in early and intermediate age-related macular disease 4 15. Klein et al 16 reported a decrease in VA of only two or fewer letters for patients displaying early age-related maculopathy lesions compared with eyes without such early lesions.…”
Section: Introductionmentioning
confidence: 99%
“…This extrafoveal vision has lower spatial resolution compared to foveal vision. Many studies on low-level visual processing have illustrated the immediate consequences of the loss of foveal vision, e.g., reduced visual acuity and contrast sensitivity (Qiu and Leat, 2009) and deficits in orientation discrimination (Bedell et al, 2009) and shape discrimination (Wang et al, 2002). For a review on psychophysical function in AMD, see Neelam et al (2009).…”
Section: Introductionmentioning
confidence: 99%
“…Computerized program can be useful to consistently provide visual stimuli, so be used in exercises of eccentric fixation to reinforce the PRL or TRL (Frennesson, Jakobsson, & Nilsson, 1995;Nilsson, Frennesson, & Nilsson, 2003;Vukicevic & Fitzmaurice, 2009). Palma et al (Palmer, Logan, Nabili, & Dutton, 2010) carried out the training program by specialist as follows: Identification of the preferred eye; Determination of the PRL using Amsler chart (Qiu & Leat, 2009); Optimal magnification and refractive correction; Lighting; Training to identify a suitable PRL by the steady eye strategy; Individualized homework to practice. This review suggested that it was necessary to apply eccentric viewing training program include two steps of determining the PRL and learn through practice for AMD.…”
Section: Discussionmentioning
confidence: 99%